Menjadi Pewarta Firman Tuhan Bercermin dari St. Paulus - Ignasius Suswakara, S.Fil.,M.Th (Atma Reksa : Jurnal Pastoral dan Kateketik, 2016)
Paul becomes the evangelizer who is militant in their era. The changes of name from Saulus (Santo Paulus) turns to Paul becomes the starting point of the forming of a tought evangelizer in delivering the faith of Jesus. Paul and his persistency has succeeded to bring the God’s words to go out from Jewish exclusifity and penetrates to the middle of other nations. That’s why, Paul can be considered as the role model to the evangelizers who lived at this era. Paul become an excellent catechist, having strong personalities, and the manner can be used as the role model to the catechist today. A Paul’s spirituality is the sample of a catechist excellent spirituality with good personality.